Analisis Dampak Wisata Dan Alokasi Anggaran Terhadap Sosial, Ekonomi, Lingkungan Masyarakat Dan Pariwisata Berkelanjutan Di Museum Geologi Kota Bandung - Maelany, Rina; Ramdani, Dadan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This research is motivated by the urgency to understand the extent to which fiscal policy is able to encourage improvements in the quality of educational tourism destinations, as well as its impact on the surrounding community. The purpose of this study is to analyze the impact of budget allocation policies on the development of the Bandung Geological Museum in three main dimensions: social, economic, and environmental. The research method used is a qualitative descriptive approach with data collection techniques in the form of field observations, brief interviews with local business actors, and supported by relevant literature studies. The results show that budget policies have played a significant role in improving museum facilities, developing interactive educational content, digitizing visitor services, and improving the quality of public services. From a social perspective, the museum has become a space for learning across ages and strengthens the community's sense of pride in Indonesia's geological richness. Economically, there has been a multiplier effect on the surrounding community, particularly micro-enterprises and street vendors. However, there are still challenges in maintaining order among informal vendors, who have not been legally integrated into the management of the tourist area. Environmentally, the museum has demonstrated a commitment to cleanliness and comfort, although improvements are still needed in the visitor information system and the presentation of audiovisual content. Overall, the Bandung Geological Museum serves as a clear example of how well-targeted budget allocation can encourage the transformation of an educational tourism destination that is not only visually appealing and educational but also has a positive impact on community welfare and environmental conservation. This study recommends the need for synergy between the government, museum management, MSMEs, and the community to ensure the sustainability of the benefits created.